Behavioral Change Promotion, Cash Transfers and Early Childhood Development : Experimental Evidence from a Government Program in a Low-Income Setting - Premand, Patrick; Barry, Oumar (World Bank, Washington, DC, 2020)
Signs of development delays and malnutrition are widespread among young children in low-income settings. Social protection programs such as cash transfers are increasingly combined with behavioral change promotion or parenting interventions to improve early childhood development. This paper disentangles the effects of behavioral change promotion from cash transfers to poor households through an experiment embedded in a government program in Niger. The study is also designed to identify within-community spillovers from the behavioral change intervention. The findings show that behavioral change promotion affects a range of practices related to nutrition, health, stimulation, and child protection. Local spillovers on parenting practices are also found. Moderate gains in children's socio-emotional development are observed, but there are no improvements in anthropometrics or cognitive development. Cash transfers alone do not alter parenting practices or improve early childhood development. Cash transfers improve welfare and food security at the household level, and the behavioral intervention induces intra-household reallocations toward children.